2014
DOI: 10.1111/sms.12262
|View full text |Cite
|
Sign up to set email alerts
|

A case of unprovoked venous thromboembolism in a marathon athlete presenting atypical sequelae: What are the chances?

Abstract: Marathon runners are exposed to multiple thrombogenic risk factors including dehydration and hemoconcentration, injury and inflammation, long-distance travel between events, and contraceptive usage. However, despite awareness about thromboembolism and several case reports detailing life-threatening hypercoagulopathies in athletes, the prevalence of venous thromboembolism in marathon runners remains uncharted. There is a lack of data and evidence-based guidelines for these athletes and for healthcare providers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…7 In addition, Kahn et al concluded that early engagement in physical exercise after an acute DVT may not only be safe but also help reduce the risk of developing post-thrombotic syndrome and its long-term adverse consequences. 8 However, several cases of unprovoked VTE, [9][10][11][12][13][14][15][16] and even of acute coronary thrombosis, 17,18 have been described in endurance athletes, suggesting that the effect of high-intensity physical exercise on blood coagulation may not be entirely dismissed. Notably, Hull and Harris identified several putative thrombogenic risk factors in endurance athletes engaged in intensive exercise for long periods of time, including dehydration and hemoconcentration, injury and inflammation, microtrauma to blood vessel walls, immobilization during longdistance travel, use of doping substances with prothrombotic potential, bradycardia and low blood pressure, thoracic outlet obstruction, and May-Thurner syndrome, along with narrowing of inferior vena cava.…”
mentioning
confidence: 99%
“…7 In addition, Kahn et al concluded that early engagement in physical exercise after an acute DVT may not only be safe but also help reduce the risk of developing post-thrombotic syndrome and its long-term adverse consequences. 8 However, several cases of unprovoked VTE, [9][10][11][12][13][14][15][16] and even of acute coronary thrombosis, 17,18 have been described in endurance athletes, suggesting that the effect of high-intensity physical exercise on blood coagulation may not be entirely dismissed. Notably, Hull and Harris identified several putative thrombogenic risk factors in endurance athletes engaged in intensive exercise for long periods of time, including dehydration and hemoconcentration, injury and inflammation, microtrauma to blood vessel walls, immobilization during longdistance travel, use of doping substances with prothrombotic potential, bradycardia and low blood pressure, thoracic outlet obstruction, and May-Thurner syndrome, along with narrowing of inferior vena cava.…”
mentioning
confidence: 99%
“…In addition, bradycardia and hypotension as a result of training are not uncommon characteristics of endurance athletes (29). Hypothetically, low circulatory blood flow at rest may increase risk of VTE, particularly in combination with long periods of tapering, low activity, and prolonged travel (ie, venous stasis); though this has yet to be examined to the best of our knowledge (11). Extreme height (ie, shorter or taller than average) may influence hemostatic balance.…”
Section: Venous Stasismentioning
confidence: 99%
“…Finally, we may conclude that prolonged endurance exercise, including ultra-endurance swimming, may alter coagulation and fibrinolysis processes, which may cause an imbalance in hemostasis, 14 particularly in aged athletes. The maintenance of proper hemostasis in marathon swimmers deserves more detailed study.…”
mentioning
confidence: 99%